ANALISIS PERATURAN DAERAH KOTA PEKANBARU NOMOR 12 TAHUN 2002 TENTANG RUKUN TETANGGA DAN RUKUN WARGA - Rizky Saputri; M. Ridwan " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study used a qualitative descriptive method. Research locations in District Charming Pekanbaru with research focus on the implementation of the City Government Regulation No. 12 Year 2002 Pekanbaru About Pillars About Pillars of Citizens. Based on this research, the analysis of Pekanbaru City Government Regulation No. 12 Year 2002 concerning the Neighborhood And Pillars of Citizens can be seen from the Evaluation and Implementation of Government Regulation No. 12 Year 2002 concerning the Neighborhood and Pillars of Citizens in District Charming Pekanbaru still less effective because in their implementation found no identification lancaranya implementation of government tasks, planning and implementation of development and sociality. In addition there are several obstacles that must be overcome in order to further the implementation of the Neighborhood Policy and the Pillars of Citizens in District Charming City can be better.Keyword: Policy Analysis, Neighborhood and Pillars of Citizens, Pekanbaru